2020
DOI: 10.2147/cmar.s253152
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA circNHSL1 Contributes to Gastric Cancer Progression Through the miR-149-5p/YWHAZ Axis</p>

Abstract: Background: Gastric cancer (GC) is a considerable health burden around the world. Circular RNA Nance-Horan syndrome-like 1 (circNHSL1) is reported to be highly expressed in GC. Nevertheless, the function and molecule mechanism of circNHSL1 are still unclear. Methods: The expression levels of circNHSL1, microRNA-149-5p (miR-149-5p) and YWHAZ were detected by real-time quantitative polymerase chain reaction (RT-qPCR). The subcellular fractionation identified the remarkable cytoplasmic localization of circNHSL1. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…We next demonstrated that miR-149-5p directly bound to CCDC6 or circDNA2 via dual-luciferase reporter gene assays and functional gain and loss experiments. Several studies 20 , 34 , 35 independently reported that miR-149-5p has a tumor-suppressive role in GC, which was consistent with our findings. In our study, the AUC for a single miR-149-5p expression level to predict the risk of GC occurrence reached 0.7102, indicating that miR-149-5p has potential as a biomarker for GC diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…We next demonstrated that miR-149-5p directly bound to CCDC6 or circDNA2 via dual-luciferase reporter gene assays and functional gain and loss experiments. Several studies 20 , 34 , 35 independently reported that miR-149-5p has a tumor-suppressive role in GC, which was consistent with our findings. In our study, the AUC for a single miR-149-5p expression level to predict the risk of GC occurrence reached 0.7102, indicating that miR-149-5p has potential as a biomarker for GC diagnosis.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have shown that circ RNA plays an important role in the occurrence and development of a variety of malignant tumors. 22 25 For example, circVAPA is highly expressed in colon cancer, 26 breast cancer 27 and liver cancer. 28 As an oncogene, circVAPA promotes the progression of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, another study demonstrated that lncRNA BLACAT1 promotes the proliferation, migration and invasion of GC cells by regulating the miR-149-5p/KIF2A axis (50). CircNHSL1 can affect the expression of YWHAZ through sponging miR-149-5p, thereby regulating the progression of GC (51). Circ_0044516 could promote the expression of HuR through sponging miR-149-5p, thereby regulating the progression of GC (52).…”
Section: Gastric Cancermentioning
confidence: 99%